PROSPECTS FOR THE USE OF MODERN NATURAL FIBERS FOR THE PRODUCTION OF MILITARY HOUSEHOLD PRODUCTS - PARASKA, OLGA; NEGORUY, VITA; REZNIKOVA, VERONIKA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes the properties of textile materials made from natural fibers and their impact on human health and the environment. It should be noted that natural fibers have excellent hygienic and vapor-permeable properties, which allows air to penetrate the fabric. This makes them comfortable to wear in different seasons and in different conditions, as they regulate body temperature and humidity. Many natural fibers, such as wool and cotton, are hypoallergenic and less likely to irritate sensitive skin than some synthetic materials. Studies have shown that natural fabrics have a range of positive properties and are not harmful to the environment. In addition, fabrics made from natural fibers have a range of health properties, which is important when creating textiles for military and household use and rehabilitation clothing. A comparative characterization of the consumer properties of natural fibers has shown that natural fibers have excellent hygienic and vapor-permeable properties, which allows air to penetrate the fabric. This makes them comfortable to wear in different seasons and in different conditions, as they regulate body temperature and humidity. Many natural fibers, such as wool and cotton, are hypoallergenic and less likely to irritate sensitive skin than some synthetic materials. In addition, products made from natural fibers can be quite strong and durable, which are valuable parameters for products, especially for military use. An equally important factor is that clothing made from natural fibers decomposes naturally, which reduces problems with waste disposal and recycling, and has a smaller environmental footprint. So, natural fibers are renewable and environmentally friendly sources of raw materials for the creation of eco-friendly military-civilian clothing. The combination of hygienic and environmental properties of natural materials is promising for the production of rehabilitation clothing and materials for the military, as well as textiles with a health-promoting effect.